Can a workbook work? Examining whether a practitioner evaluation toolkit can promote instrumental use. (October 2015) - Campbell, Rebecca; Townsend, Stephanie M.; Shaw, Jessica; Karim, Nidal; Markowitz, Jenifer
Highlights: We developed a practitioner evaluation toolkit for sexual assault nurse examiners, which was implemented in a multi-site, national-scale project. We studied how the nurse practitioners used the toolkit and whether they used the findings to improve local practice (i.e., instrumental use). Results showed that all six programs were able to design and implement methodologically rigorous evaluations. All six sites showed evidence of instrumental use of their findings to change local practice and community protocols for the care of sexual assault victims. Abstract: In large-scale, multi-site contexts, developing and disseminating practitioner-oriented evaluation toolkits are an increasingly common strategy for building evaluation capacity. Toolkits explain the evaluation process, present evaluation design choices, and offer step-by-step guidance to practitioners. To date, there has been limited research on whether such resources truly foster the successful design, implementation, and use of evaluation findings. In this paper, we describe a multi-site project in which we developed a practitioner evaluation toolkit and then studied the extent to which the toolkit and accompanying technical assistance was effective in promoting successful completion of local-level evaluations and fostering instrumental use of the findings (i.e., whether programs directly used their findings to improve practice, see Patton, 2008 ). Forensic nurse practitioners from six geographically dispersed service programs completed methodologically rigorous evaluations; furthermore, all six programs used the findings to create programmatic and community-level changes to improve local practice. Implications for evaluation capacity building are discussed.